Experimental investigation of the shear mechanical behavior of sandstone under unloading normal stress. (February 2019) - Zhu, Tantan; Huang, Da
Abstract: Excavations in rocks always induce unloading of stress in excavation-disturbed zones. In many cases, rocks fail due to shear under unloading normal stress. To study the shear mechanical behavior of sandstone under unloading normal stress, a new loading path was proposed, and direct shear tests under unloading normal stress were performed on sandstone samples. For the unloading test, normal stress was first applied, and then, shear stress was gradually applied to a desired level. After that, the normal stress was unloaded until the sample failed. The shear and normal displacements, shear strength, failure criterion and failure pattern were analyzed. Three characteristic displacements, i.e., the failure shear displacement D f, the shear displacement of unloading D su, and the normal displacement of unloading D nu, were also analyzed in detail to describe the evolution of shear and normal deformation during the tests. The results indicated that the initial normal stress and initial shear stress significantly influence the three displacements, except for the shear displacement of unloading D su, which is not sensitive to varying initial shear stress. Shear displacement shows linear growth at the initial stage of unloading normal stress and then increases nonlinearly and rapidly immediately before failure occurs. The failure normal stress increases linearly with the initial shear stress, while the failure normal stress grows exponentially as the initial normal stress increases. The Mohr-Coulomb criterion describes well the change in shear strength with varying initial shear stress. Compared to the direct shear test under constant normal stress, cohesion in the direct shear test under unloading normal stress decreases noticeably, while the internal friction angle increases slightly.